The applicability of the concept of treatment adherence in the context of the Brazilian mental health system - Patricia Elizabeth Sanz de Alvarez; Ernestina Rosendo; João Carlos Alchieri (SciELO, 2016)
Objective To present reflections on the type of research conducted on a treatment adherence among users of Public Mental Health System in Brazil and discuss the applicability of the concept of adherence to treatment in this context. Method Literature review in SciELO, LILACS, Cochrane Library and PubMed / MEDLINE using the Health Sciences Descriptors (DeCS) treatment, adhesion and "mental health" and the specific vocabulary of the Medical Subject Headings (MeSH) "patient compliance/psychologist" y "mental health". They were included for review the complete texts and theses published between 2007-2012 in Portuguese, English and Spanish. Results 127 articles were recovered, 32 specifically related to mental health. Eight were excluded for duplicates and after reading the remaining 24 articles were selected for this study 10 conducted in the field of Mental Health in Brazil. No investigations have been identified with focus on adherence to psychosocial treatment offered in public mental health. Conclusions disregard of the mental health legislation and reinforce the asylum model of assistance.